2006
DOI: 10.1016/j.rmed.2005.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Thin-section CT assessment of spontaneous pneumomediastinum in interstitial lung disease: Correlation with serial changes in lung parenchymal abnormalities

Abstract: Spontaneous pneumomediastinum associated with interstitial lung disease appears to have a tendency to occur under conditions of altered of parenchymal interstitial lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…Matsuoka et al (17) described significant decrease in the extent of opacification in patients who received either corticosteroids or immunosuppressive agents for ILD at the time their pneumomediastinums were detected when the CT images were compared with CT images taken before these patients developed pneumomediastinum. Progressions of honeycombing scores were not evident in our case when pneumomediastinum was diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Matsuoka et al (17) described significant decrease in the extent of opacification in patients who received either corticosteroids or immunosuppressive agents for ILD at the time their pneumomediastinums were detected when the CT images were compared with CT images taken before these patients developed pneumomediastinum. Progressions of honeycombing scores were not evident in our case when pneumomediastinum was diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the majority of the patients with concomitant pneumomediastinum were receiving corticosteroids for underlying lung disease. Matsuoka et al reviewed computed tomography images before and at the time of detection of pneumomediastinum in patients with ILD and reported that pneumomediastinum had developed in the patients receiving corticosteroids despite the decrease of lung opacities including ground-glass opacity and consolidation (28). Therefore, corticosteroid use may be associated with the development of pneumomediastinum.…”
Section: Discussionmentioning
confidence: 99%
“…One report suggested that the use of corticosteroids for the treatment of underlying diseases weakens the interstitial lung tissues, 7 while another suggested that spontaneous pneumomediastinum occurs if steroid or immunosuppressant therapy is not administered to patients on worsening of their condition. 8 All these reports focused on air leaks as the underlying pathology.…”
Section: Discussionmentioning
confidence: 99%